ETIKA PROFESI POLISI - Linda Safitri; M. Fatih Al Khusni; Ulan Agung (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research will discuss what the police professional code of ethics is. Ethics comes from the Greek